Ethical Thinking From The Perspective Of Social Responsibility Theory And Its Effects On Media Practice - أحمد جبار (International Journal of Social Communication, 2019)
Ethical values and ideals intersect with different human societies, with the aim of balancing and harmonizing their members and controlling their behaviors. In this light, the problem of defining the concept of ethics raises a lot of controversy among scholars in terms of reference and reference, whether religious, cognitive or descriptive. Many researchers in media and communication science from the point of view of ethical censorship of the media practice of professionals in journalism, how to reconcile the principles of "freedom" and "responsibility" While respecting people's beliefs and not jumping on customs and traditions that threaten the stability of society and arousing public feelings and not endangering public morality, was the theory of social responsibility in this light to contain the concept based on the deviation that occurred in the media?